2015
DOI: 10.1038/nrendo.2015.211
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids — at the crossroads between the gut microbiota and host metabolism

Abstract: Various metabolic disorders are associated with changes in inflammatory tone. Among the latest advances in the metabolism field, the discovery that gut microorganisms have a major role in host metabolism has revealed the possibility of a plethora of associations between gut bacteria and numerous diseases. However, to date, few mechanisms have been clearly established. Accumulating evidence indicates that the endocannabinoid system and related bioactive lipids strongly contribute to several physiological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
267
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(276 citation statements)
references
References 154 publications
6
267
1
2
Order By: Relevance
“…Gut microbiota along with disrupted gut barrier function is an important component in metabolic disorders in particular obesity, hepatic steatosis, and diabetes-all characterised by persistent low-grade inflammation (55). Pre-clinical studies showed that procalcitonin precursors circulate freely in the blood under normal physiological conditions with elevated circulating levels at time of severe infection or systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota along with disrupted gut barrier function is an important component in metabolic disorders in particular obesity, hepatic steatosis, and diabetes-all characterised by persistent low-grade inflammation (55). Pre-clinical studies showed that procalcitonin precursors circulate freely in the blood under normal physiological conditions with elevated circulating levels at time of severe infection or systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Obese subjects show higher eCB levels, which can be increased via HFD and reduced by prebiotic treatment as well as antibiotic treatment [122]. Chronic CD receptor stimulation induced glucose intolerance, stimulated metabolic inflammation, and altered lipid storage in skeletal muscle [116], [123].…”
Section: The Gut Microbiota Alters Satiety Signalingmentioning
confidence: 99%
“…[71][72][73][74] However, low dose LPS also promotes glucose-stimulated insulin secretion by up-regulating IL-6 mediated GLP-1 production and thus lower blood glucose levels ( Figure 5), 48,75 indicating a protective effect of LPS on glucose homeostasis.…”
Section: Lipopolysaccharide (Lps) In Glucose Homeostasis and Obesitymentioning
confidence: 99%